2014
DOI: 10.1557/jmr.2014.284
|View full text |Cite
|
Sign up to set email alerts
|

The effects of surface modifications of multiwalled carbon nanotubes on their dispersibility in different solvents and poly(ether ether ketone)

Abstract: The effects of surface modifications of multi-walled carbon nanotubes (MWCNTs) on their dispersibility in different solvents and poly (ether ether ketone) (PEEK) have been studied. MWCNTs were treated by mixed acids to obtain acid-functionalized MWCNTs. The acid-functionalized MWCNTs were modified with six different chemical agents separately, 1,6-diaminohexane, hexadecyl trimethyl ammonium bromide, silane coupling agent 3-aminopropyltriethoxysilane, anhydrous sulfanilic acid and ethanolamine. MWCNT/PEEK compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Rong 80 and Cheng et al 81 followed such dispersingmixing-drying-extruding procedure to prepare CNT/ PEEK composites containing acid-functionalized (up to 5 wt%) and polyethersulfone (PES)-functionalized CNTs (1 wt%), respectively. Cao et al 82 also mixed various surface-modified CNTs and PEEK directly in solution to evaluate the effect of surface modification. Using this dispersion-based compounding method, other functional particles can be incorporated into CNT/PEEK nanocomposites.…”
Section: Preparation Methodsmentioning
confidence: 99%
“…Rong 80 and Cheng et al 81 followed such dispersingmixing-drying-extruding procedure to prepare CNT/ PEEK composites containing acid-functionalized (up to 5 wt%) and polyethersulfone (PES)-functionalized CNTs (1 wt%), respectively. Cao et al 82 also mixed various surface-modified CNTs and PEEK directly in solution to evaluate the effect of surface modification. Using this dispersion-based compounding method, other functional particles can be incorporated into CNT/PEEK nanocomposites.…”
Section: Preparation Methodsmentioning
confidence: 99%
“…As can be seen from Figure characteristic peaks obviously increased after the chemical treatment. It showed that CNTs were tightly packed with each other after modification, and the number of carbon tubes in unit volume increased [31,32]. Figure 8 represents the FT-IR spectrum of (a) vibration peak of methylene (-CH 2 -), which indicated that the structure of methylene was not changed by oxidation.…”
Section: Xpsmentioning
confidence: 99%
“…The supernatant was removed and the sediment was washed by deionized water until neutral. The product was dried in a vacuum oven at 80°C for 24 hours and marked as a-MWCNTs in which hydroxyl and carboxyl groups were grafted on the surfaces of MWCNTs [19], as shown in Fig. 1(a).…”
Section: Preparation Of Acid-functionalized Mwcntsmentioning
confidence: 99%
“…Then, the solution and a-MWCNTs dispersion were mixed in a flask and the reaction was allowed to proceed under magnetic stirring at 50°C for 10 hours. Finally, the reaction mixture was washed with ethanol and water respectively and dried under vacuum at 80°C for 24 hours to obtain the product marked as e-MWCNTs, and amino groups were grafted on the surfaces of MWCNTs [19], as shown in Fig. 1(b).…”
Section: Grafting Of Ethanolamine To Mwcntsmentioning
confidence: 99%